A comparison of Bygholm feed sieve to standard particle-size analysis techniques - C K Benz; C N Groesbeck; Michael D Tokach; Jim L Nelssen; Robert D Goodband; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2005)
Three experiments were conducted to evaluate the Bygholm Feed Sieve particle size tester. The Bygholm Feed Sieve is an 11 inch × 2.25 inch × 4.25 inch plastic box divided into four compartments by three different screen sizes (3,000-, 2,000-, and 1,000-micron mesh). In Experiment 1, particle size was determined for 20 ground corn samples with a Ro-Tap 13-sieve stack (53- to 3,350-micron Tyler mesh screens).The particle sizes ranged from 543 to 1,741 microns. Samples were analyzed for particle size with the standard Bygholm Feed Sieve, operated according to the manufacturer's directions. In Experiment 2, two rubber balls were placed on the 2,000 micron screen and one ball was placed on the 1,000 micron screen in the Bygholm Feed Sieve to aid in moving particles through the screens. Samples were then analyzed for particle size, according to the manufacturer's directions. In Experiment 3, 24 additional samples with particle sizes ranging from 604 to 1,305 microns were analyzed to determine the accuracy of the regression equation created by Experiment 1. After initial analysis indicated that the equation didn't accurately predict particle size of samples with a large particle size, an additional 11 samples with particle sizes ranging from 1,054 to 1,741 microns were analyzed. After this analysis, all samples from Experiments 1 and 3 were used to develop a new set of regression equations to calculate the particle size of samples over a wider micron range. The Bygholm Feed Sieve more accurately predicted the particle size of samples when rubber balls were not present within the system (RÂ² = 0.88 versus 0.82). The regression equation created by Experiment 1 predicted 90% of the samples to be within 100 microns of the actual particle size when the samples were less than 1,000 microns. When samples are coarser than 1,000 microns, however, the regression equation created by Experiment 3 should be used; it predicts 85% of the samples to be within 100 microns of the actual particle size when the samples were larger than 1,000 microns and 98% of all samples to be within 150 microns of the actual particle size.; Swine Day, 2005, Kansas State University, Manhattan, KS, 2005
Keywords: Swine day; 2005; Summary Publication of Report of Progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 964; Kansas Agricultural Experiment Station contribution; no. 06-63-S; Swine; Particle size; Ground corn; Bygholm feed sieve